Kreativitas Kesenian Bangkong Reang Oleh Grup Kesenian Gema Panglipur Kampung Cijaura Kecamatan Ciwidey - Anna Ratuna Aureylia (Paraguna, 2022)
Bangkong Reang art is a typical Sundanese art that grows and develops in the agrarian area. This art is influenced by the ecosystem in the area, but its existence is now less preserved along with the entry of outside cultures. The creativity of the Gema Panglipur Art Group was able to maintain the art of Bangkong Reang in the midst of the outbreak of foreign culture.